Problematika Pembelajaran Tahfidzul Qur’an di Madrasah Tsanawiyah Negeri 4 Kabupaten Pasaman - Wahyuni, Septia; Monia, Fenny Ayu; Ilasmi, Erma (Indonesian Research Journal on Education, 2023)
Tahfidz al-Qur'an is one of the processes of guarding and maintaining the purity of the holy book of the Qur'an. Memorizing the Qur'an is a very noble duty and responsibility, everyone can memorize it but not everyone can memorize it well. This study aims to determine the problems of learning tahfidz al-Qur'an by providing solutions to overcome these problems. This research was conducted at MTsN 4 Pasaman,Bonjol District, Pasaman Regency, especially in class VII.1, using a qualitative approach and descriptive method. Data collection techniques used in this study are observation and interviews. Interviews were conducted with teachers and several students of class VII.1 MTsN 4 Pasaman. Then the data that has been collected, is analyzed using qualitative data analysis techniques.